Microbiology - Batzing, Barry L.
Batzing's MICROBIOLOGY: AN INTRODUCTION offers a new approach in introductory microbiology, with an emphasis on teaching effectively the important concepts of the course without a strict focus on memorization. Pedagogical material, such as concept maps and flow diagrams, is carefully integrated throughout to enhance understanding and gives students a visual representation of difficult topics. The final portion of the text follows a portal of entry, or route of transmission organization, with material presented around the method by which microbes enter the host's body